STRATEGI TEBANG PILIH SEBAGAI ALTERNATIF PENGEMBANGAN KOPERASI DI KABUPATEN JEMBER - M. Fathorrazi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2010)
This research was intended to carry out a mapping on the existing cooperatives in Jember Regency using ICA Grid Model. Mapping results would indicate which cooperatives should be developed and which ones do not need supervision, so that this is expected to be a consideration for the Government of Jember Regency for its cooperative development.Based on the analysis, it was concluded that in average cooperatives in Jember Regency were in quadrant I because the value of implementation of the cooperative principles had positive value, and the competitiveness also had a positive value. This means that at average cooperatives in Jember Regency belong ideal and feasible cooperatives to be developed. When viewed on each district, it was seen that there are several cooperatives that were in quadrant II, that is, cooperatives that had properly applied their identity but were still very dependent on government, including cooperatives in Districts of Mayang, Arjasa, Ledok Ombo, Suber Jambe, Tanggul, and Silo and Tempurejo. The remaining were already ideal co-operatives.Keywords: “Tabang Pilih” strategy, Cooperative development